Rethinking Regulatory Engagement Theory - Pham, Michel Tuan; Avnet, Tamar (Journal of Consumer Psychology, 2009)
AbstractWe offer a constructive critique of Regulatory Engagement Theory (Higgins, E. T. (2006). Value from hedonic experience and engagement. Psychological Review, 113(3), 439–460.; Higgins, E. T., and Scholer, A. A. (2009). Engaging the consumer: The science and art of the value creation process. Journal of Consumer Psychology, 19(2).). After highlighting the major tenets of the theory and its main contributions, we identify some of its conceptual ambiguities. We then argue that the hedonic and intensity components of value may not be psychologically separable in that experiences acquire their hedonic quality through their intensity. We next discuss why the various determinants of strength of engagement proposed by the theory may not all operate through the same process. Even the regulatory fit phenomenon seems to involve more than one process. We conclude by suggesting that many strength‐of‐engagement effects may reflect feelings‐as‐information inferences consistent with the Generalized Affect‐as‐Information Model of judgment (GAIM; Pham, M. T. (2008). The lexicon and Grammar of Affect‐as‐Information: The GAIM. In M. Wanke (Ed.), Social psychology of consumer behavior. New York: Psychology Press.).